Preferred practice guidelines for glaucoma management during COVID-19 pandemic - Sushma Tejwani (Indian Journal of Ophthalmology, 2020)
The COVID-19 pandemic has threatened the humanity at a global level to a large extent by the burden of the disease with significant mortality and to a certain extent as a byproduct of the necessary efforts to contain the same. There is a significant impact on the health care system, as we not only have to contain pandemic, but continue to treat our non-COVID-19 patients in a safe and responsible manner. Ophthalmology practice in general and glaucoma in particular needs certain modifications and additional precautions while examining as well as managing these patients keeping their and our safety in mind. As the lockdown relaxations are in vogue we need to learn how to deal with our regular patients as well in addition to emergency care. This paper presents the consensus-based guidelines by an expert panel on how to restart glaucoma practice during this COVID-19 time. These guidelines will be applicable across the country and should help ophthalmologists and glaucoma specialist to restart their practices while safeguarding the patients and their own selves from getting infected.